2010
DOI: 10.1021/nl1021706
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength Plasmonic Lasing from a Semiconductor Nanodisk with Silver Nanopan Cavity

Abstract: We report the experimental demonstration of an optically pumped silver-nanopan plasmonic laser with a subwavelength mode volume of 0.56(lambda/2n)(3). The lasing mode is clearly identified as a whispering-gallery plasmonic mode confined at the bottom of the silver nanopan from measurements of the spectrum, mode image, and polarization state, as well as agreement with numerical simulations. In addition, the significant temperature-dependent lasing threshold of the plasmonic mode contrasts and distinguishes them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
173
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(177 citation statements)
references
References 30 publications
2
173
0
Order By: Relevance
“…4c) 69 or whispering gallery mode cavities (Fig. 4d) 70,71 can be obtained by patterning either the dielectric near the metal interface or the metal itself. For plasmon mode cavities, the electromagnetic field in the transverse direction is evanescent and so the transverse dimensions of the optical mode and device can be much smaller than 2 ⁄ .…”
Section: Small Laser Types and Their Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…4c) 69 or whispering gallery mode cavities (Fig. 4d) 70,71 can be obtained by patterning either the dielectric near the metal interface or the metal itself. For plasmon mode cavities, the electromagnetic field in the transverse direction is evanescent and so the transverse dimensions of the optical mode and device can be much smaller than 2 ⁄ .…”
Section: Small Laser Types and Their Characteristicsmentioning
confidence: 99%
“…Like small dielectric lasers, the more recently developed small metallic and plasmonic lasers can be realized with a widely varying range of laser resonator structures, from plasmonic photonic crystal structures and open dielectric-loaded waveguides 20,[69][70][71]74,81,92,93 to small encapsulated devices or metallic nano-particle resonators [17][18][19][63][64][65] . There is potential for further development of different forms of metallic waveguides, permitting possibly better tradeoffs between small volume and metal induced losses.…”
Section: Future Trends and Challengesmentioning
confidence: 99%
“…Spasers and plasmonic nanolasers with deep subwavelength cavities represent one of the important frontiers of research in nanophotonics and nanotechnology in general. [1][2][3][4][5][6][7][8][9][10] While metals have been used as parts of the laser cavity for long wavelengths, 11 it remains an open question if metals such as silver or gold can be used to make a subwavelength cavity in the near infrared or shorter wavelength, due to dramatically increased metal loss in these wavelengths, especially at RT. 12 Theoretical studies 10,13 that accounted for wavelength compression and metal loss near surface plasmon polariton (SPP) resonance showed that it was indeed possible to realize a net positive gain in a semiconductor-metal core-shell structure.…”
mentioning
confidence: 99%
“…This was soon verified in an experiment with a semiconductor-metal core-shell structure. 3 While great progress has been made in the past few years in nanolasers with deep subwavelengthsized metal cavities [1][2][3][4][5][6][7][8] and spacers, 2,9 the realization of RT continuous wave (cw) operation under electrical injection has remained elusive. Despite intensive activities worldwide, subwavelength-cavity RT lasing has been demonstrated only under optical [5][6][7] or electrical-pulse pumping, 4 or under cw electrical pumping but at low temperature.…”
mentioning
confidence: 99%
“…Any remaining doubt about metallic structure was quickly removed by the first experimental demonstration by Hill et al 14,15 For any practical applications, a subwavelength metallic nanolaser should be able to operate under continuous wave ͑cw͒ electrical injection at room temperature. Currently, reported metallic lasers are limited to optical pumping, [16][17][18][19][20][21] larger dimension than wavelength, 22 or cw lasing at liquid nitrogen temperature or room temperature operation under pulse current injection. 23 Achieving cw lasing under electrical injection at operating temperatures higher than liquid nitrogen temperature would be an important milestone in eventually realizing room temperature lasing.…”
mentioning
confidence: 99%